CALCULATION SPECIFICATION OF ACOUSTIC SCREENS LOCATED IN PRODUCTION AREA - Veronika Alexandrovna Bondarenko; Igor Vladimirovich Boguslavskiy; Sergey Sergeyevich Podust (Advanced Engineering Research, 2014)
Acoustic screens are one of the means to provide sound insulation and noise reduction on its path fr om the source to the target point (TP, the workplace). The advantages of the acoustic screens are constru c tive simplicity, light weight, and relat ively low cost. A distin c tive feature of an acoustic screen as a sound insulation system is that the area of maximum attenuation is located in close proximity to the screen. The efficiency effect of th e screens is d etermined by the following factors: - a sm all size of the noise source; - the conversion of high - frequency components of the source noise spectrum; - the location of the work area outside the technological machine; - a short distance from the noise source to the operator's station. All that fully applies to the equipment for various applications, in particular, for the metal and woodworking machinery (lathe, milling, grinding), gear - boxes, and engines on the running sites. The existing d e tailed screen calculations are designed for screen installati on. At free atmosphere, the formation of the acoustic field under the screen insta llation inside the production areas differs essentially due to the multiple reflections of sound waves. The studies on the acoustic performance of screens inside the produ c ti on are resulted in the paper.